Spanish Hospital at Ontiniente : inter-departmental correspondence (copy) - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
042-0003-001 H.B. MORGAN. Sir WALTER CITRINE. Social Insurance. 23rd August, 1937 SPANISH HOSPITAL AT ONTINIENTE. Dear Sir Walter, I am attaching hereto my report on my visit to Ontiniente. The report is an honest, impartial account of my inspection of the Hospital. The hospital is not, of course, up to the standard of any of the best ordinary hospital in Great Britain, nor even of the best L.C.C. hospitaIs, and not yet I think up to the standard of some of the best hospitals in Germany and Scandinavia, but as compared with any other hospital I saw in Spain, or most hospitals in other Continental countries, I have no hesitation in adhering to my opinion mentioned in the report. I think the work of the I.F.T.U. at the base at Ontiniente is the best medical aid work that I saw in Spain, and I feel sure that concentration on a base hospital, an efficient, effective, well-administered base hospital, is better medical aid and of more lasting value to the Spanish people than the glamour of any work, however well and meritoriously performed with risk of danger, nearer the front line. Yours sincerely, H.B.M. Medical Adviser. E.K. 292/946/42/3